Isolation and characterization of potential proteolytic and amylolytic bacteria from Bayanan hot spring as bioremediation agents - Santosa, Slamet; Setiyaningrum, Erma Nur (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Hot water temperature can be a place for the development of thermophilic bacteria. Thermophilic bacteria produce thermostable enzymes which are needed in various industrial fields such as agriculture, food, detergent, pharmacology, and bioremediation agents. This study aims to isolate and characterize potential proteolytic and amylolytic bacteria from the Bayanan hot spring. Samples were collected from two distinct locations within the geothermal environment: the hot spring source itself and the associated water storage pools. The collected samples underwent a dilution and isolation process to obtain pure bacterial cultures. Subsequently, these isolates were inoculated onto selective media, including skim milk agar (SMA) and nutrient agar (NA), to assess their proteolytic and amylolytic activities, respectively. The presence and extent of these enzymatic activities were determined by measuring the diameter of the clear zone surrounding each bacterial colony. The analysis revealed the presence of eight proteolytic bacterial isolates and twenty amylolytic isolates. Notably, a hydrolysis index threshold of ≥2.5 was implemented to identify isolates with high potential for proteolytic and amylolytic activity. Based on this criterion, two proteolytic bacterial isolates (codes B2-12-C3 and B1-12-B3) exhibited a proteolytic index exceeding 2.5. Furthermore, eight amylolytic isolates displayed an index above 2.5 (codes B1-10-A1, B1-10-A3, B2-8-A1, B2-8-A2, B2-10-A1, B2-10-A2, B2-12-C1, and B2-12-C2). These isolates, particularly those with high hydrolysis index values, has potential as bioremediation agents due to their demonstrated ability to efficiently hydrolyze proteins and starches.